Sorghum plants with ratoon cultivation increase production and income. Issue 1 (November 2021) - Syuryawati,; Faesal,; Aqil, Muhammad
Abstract: Sorghum has broad adaptability, drought tolerance, high production, has strong and deep roots so that it can grow back after being harvested (ratoon) which can reduce production costs, with ratoon sorghum cultivation it can increase production and income. This study aims to determine the benefits of sorghum farming with ratoon cultivation which can increase farmers' production and income. Research was conducted in Jeneponto Regency, South Sulawesi, March- September 2018. Research consisted of eight sorghum lines andNumbu variety, using Randomize Block Design of three replications. Spacing 75 cm x 20 cm 1 plant/hole. The main fertilizing plants were 300 kg urea + 100 kg SP36 + 100 kg KClha −1, and ratoon plants were 150 kg urea + 50 kg SP36 + 50 kg KClha −1 . Results showed that average yield of main crop was 5.92-6.57 tha −1, and ratoon 4.85-5.83 tha −1 . Revenue obtainedmain cropRp. 11, 840, 000-13, 140, 000 andratoonRp. 9, 706, 000-11, 660, 000ha −1 . Benefit of sorghum farming using ratoon system is Rp. 4, 843, 000-5, 950, 000ha −1, and Rp.6, 729, 000-Rp. 8, 572, 000ha −1 forratoon system. with two harvests, farming benefits range from Rp. 11.5 million-14.5 millionha −1 . This is supported by efficient use of sorghum ratoon farming to produce 1 kg of sorghum seeds at a cost of only Rp. 530-615 or more cost efficient up to 49.47% of main crop. Thus, sorghum farming with ratoon cultivation is very helpful for farmers because there is additional production and income so that it is feasible to develop.